Evaluation of the Darcy velocity and porosity in a Ryukyu limestone aquifer - SUZUKI, Mariko; TAKAHASHI, Yoshitaro; MAENO, Itsuki; INOUE, Kazuya; KURASAWA, Tomoki (Chikasui Gakkai shi, 2022)
In this study, we conducted single-borehole dilution tests (SBDTs) to estimate the Darcy velocity in a Ryukyu limestone aquifer. Also, 93 core samples of Ryukyu limestone at the field were collected, and the porosities were determined gravimetrically. By comparing the Darcy velocities estimated from SBDTs and the ambient hydraulic gradient at the field, the validity of SBDTs was verified. On the other hand, the average porosity for 93 core samples was 29.6％, which was larger than the published literature value. This is due to the fact that the aquifer is composed of the lower Ryukyu limestone.